PERSUASIVE UTTERANCE FOUND IN SHOP AND RESTAURANT : AN ANALYSIS OF SPEECH ACT IN PERSUADING VISITORS OF A STORE IN BANDUNG, WEST JAVA AND “MR. JUNETO” RESTAURANT IN SOLO, CENTRAL JAVA - Silviana Masran (Menara Ilmu, 2018)
This writing is aimed to describe the linguistic phenomenon of speech act inpersuasive. The objective of this writing is to identify the strategies in persuading visitors inshop and restaurant in Bandung and Solo. The data are containing persuasive utterances inshop and restaurant in Bandung, West Java and Solo, Central Java. In collecting data, theobservational method is employed throughout attentive method and taking picture. The dataare analyzed by referential and pragmatic identity method. The analysis is related to theconcept proposed by Searle (1979). The result of analysis is descriptively done.Keyword: Speech act, function, Strategy, Persuasive